Integration of Bentengan Traditional Games in Science Learning to Improve Preschool Children's Cognitive and Motor Development - Sari, Diah Andika; Mapunda, Waziri Mohamed; Bayan, Rocelia Pasco; Asyhari, Ardian (Jurnal Pendidikan IPA Indonesia, 2025)
This study confirms that the traditional game Bentengan can serve as a contextual model for early childhood science learning, effectively integrating cognitive, motor, and social-emotional development. Empirical evidence suggests that embodied interaction during play enhances preschoolers’ conceptual understanding of force, motion, balance, and environmental phenomena, while also strengthening their gross and fine motor coordination. Theoretically, these findings contribute to embodied cognition studies by demonstrating how sensorimotor engagement functions as a foundation for abstract scientific reasoning in STEM domains. Practically, the integration of culturally grounded games provides a locally relevant and engaging alternative to conventional instruction, positioning Bentengan as a sustainable approach for culture-based preschool education that aligns with current curriculum reforms and the broader agenda of inclusive, active, and meaningful early science education.